As águas dos gerais: uma proposta de ensino contextualizada para ciências/geografia - Tânia Cássia Ferreira de Sousa (2023)
The present research entitled “The waters of Gerais: a contextualized teaching proposal for Science/Geography” aimed to develop a teaching proposal based on the generating theme "The waters of Gerais", in order to establish a dialogue between the scientific contents of science and geography and the knowledge and environmental perceptions of the Geraizeiros in relation to the water theme. This theme arose from reflections and concerns about teaching-learning in field education and from my teaching practice. This is a qualitative research, for which semistructured interviews were carried out with some Geraizeiros in order to identify their traditional knowledge related to the topic of water and the climatic dynamics of the region they call Gerais, located in the municipality of Rio Pardo de Minas. The data collected from these interviews were important for the development of the teaching proposal, as it allowed us to raise issues related to the local reality and include them in the proposed teaching activities. The Geraizeiros are people traditionally known by this name who have a strong connection to the extraction of Cerrado fruits and who have their own way of managing and cultivating the land and raising animals on communal lands: the chapadas. The Geraizeiros have a very special relationship with water. Thus, the relevance of this theme in science and geography classes is related to its importance for the lives of the people in the communities where the students live, since the availability and quality of water are crucial for the maintenance of the Geraizeiros' work and culture, whether in the irrigation of small areas (fields, gardens, and backyards) or in the processing of products in small agro-industries. To put Field Education into practice, it is necessary that teaching practices dialogue with the political, social, environmental, and cultural contexts of the countryside, incorporating contents and methodologies that relate to reality and that value the way of life, culture, wishes, and knowledge of peasant subjects. It is in this perspective that this research intends to contribute to Field Education.